Evaluating the role of HER2-low versus HER2-0 status in predicting response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Topal, Alper; Başak, Mustafa (The European Research Journal, 2025)
Objectives: The classification of human epidermal growth factor receptor 2 (HER2)-low breast cancer has gained clinical relevance following the success of antibody-drug conjugates in this subgroup. However, its prognostic and predictive role, particularly in hormone receptor-positive (HR+) early breast cancer treated with neoadjuvant chemotherapy (NACT), remains unclear. This study aimed to evaluate the impact of HER2-low versus HER2-0 status on pathological complete response (pCR) and disease-free survival (DFS) in HR+ breast cancer patients undergoing NACT. Methods: A total of 216 HR+ and HER2-negative early breast cancer patients treated with NACT at Tokat Gaziosmanpasa University Hospital between January 2014 and January 2024 were retrospectively analyzed. HER2-low was defined as IHC 1+ or 2+ without gene amplification by FISH. pCR was assessed via the Miller-Payne grading system. Survival analyses were conducted using the Kaplan-Meier method; multivariate analyses were performed using Cox regression. Results: Of the 216 patients, 30 (13.9%) achieved pCR. There was no statistically significant difference in pCR (P=0.83) or DFS (P=0.12) between HER2-0 and HER2-low groups. However, patients with ER